What is the burden of tinnitus? - Pryce, Helen; Dauman, Nicolas; Burns-O’Connell, Georgina (Frontiers in Psychology, 2023)
Abstract Tinnitus is a perception of a sound that occurs as a result of auditory pathway stimulation in the absence of an external stimulus. From the patient’s point of view this is a complex experience that often occurs alongside other health conditions, including hearing loss. The experience of tinnitus occurs in a context where health services are seeing a rise in multi-morbidity and complexity of health conditions. As we age, we can expect to live with multiple health conditions. In tinnitus, as with most chronic health conditions, the largest treatment workload is devolved to the patient. Patients are required to implement treatments, learn about tinnitus and find new ways of coping. Yet this work happens invisibly, without recognition from clinicians who measure outcomes but not the efforts made to achieve outcomes. Patient-centered care depends upon the recognition of the cumulative burdens that patients experience. This paper will describe the cumulative burdens of tinnitus, both the experience of hearing the tinnitus and from the treatments undertaken. This paper will be the first to apply ‘burden of treatment’ theory to examine the experience of tinnitus. It will explore patient experiences of self-management and highlight potential areas where care can be improved.